Discussion on the implications upon the environment of some technologies from the second green revolution - Montoya Rojas, Grace Andrea; Barragan, Claudia B; Herrera Aranguren, Miguel; Martínez Hernández, Neils A.; Rodríguez Tolosa, Rosa I.; Villamil Gil, Rosa Shirley (TECCIENCIA, 2014)
The Second Green Revolution explores genetic progress based on the application of modern biotechnology to agriculture, seeking to improve agricultural practices and products. Likewise, its main aspect is the creation of genetically modified organisms (GMO), best known as transgenics. The Second Green Revolution implies using techniques like micro-propagation, genetic engineering, and – more recently – using bacteria as potential bio-fertilizer, among them nitrogen-fixing, phosphate-solubilizing, and auxin producer bacteria, etc. Genetic engineering groups techniques of gene identification, selection, transference, and control, with transgenesis being the genetic engineering technique most applied in agriculture. With the tools, techniques, and methodologies of modern biotechnology, it is possible to more quickly produce new plant varieties than before, with improved nutritional characteristics, tolerance to adverse conditions, resistance to specific herbicides, and pest control. Soil integrates environmental components and permits development of life, life which in turn forms soils offering broadly diverse ecosystemic opportunities, constantly nourishing and producing food for all species, including man. However, the alteration of the soil-forming factors, due to natural cycles or man’s intervention, impacts notably on its productivity and the temporality demanded by humans. Between supply and demand an increasingly broadening gap is forged and the dehumanization of territories when trying to schematize nature, offers opportunities to science to meet needs with different techniques.